Epidemiological transition of metabolic dysfunction-associated steatotic liver disease-related chronic liver disease and cirrhosis: a comparative study between China and the global population (1990–2021) - Tang, Yi; Gu, Changhao (Frontiers in Nutrition, 2025)
ObjectivesThis study systematically evaluates the epidemiological transition of metabolic dysfunction-associated steatotic liver disease (MASLD)-related chronic liver diseases (CLD) and cirrhosis burden in China versus global populations (1990–2021), with emphasis on age-sex stratified disparities in incidence, prevalence, mortality, and disability-adjusted life years (DALYs). We aim to identify critical intervention windows for precision public health strategies.MethodsUsing open data from the Global Burden of Disease (GBD) database from 1990 to 2021, we conducted a comparative age-period-cohort analysis between Chinese and global populations. Joinpoint regression quantified temporal trends through average annual percentage change (AAPC) with 95% confidence intervals. Multidimensional stratification by age-sex cohorts elucidated differential burden patterns across disease progression stages.ResultsFrom 1990 to 2021, China’s age-standardized incidence rate (ASIR) increased from 495.16 per 100,000 population in 1990 to 621.18 per 100,000 in 2021 (AAPC = 0.74%). The age-standardized prevalence rate (ASPR) rose from 12,787.39 per 100,000 to 15,606.31 per 100,000 (AAPC = 0.63%). Globally, the ASIR increased from 475.18 per 100,000 to 592.78 per 100,000 (AAPC = 0.71%), while the ASPR increased from 12,084.69 per 100,000 to 15,017.46 per 100,000 (AAPC = 0.71%). China’s age-standardized mortality rate (ASMR) declined from 0.54 per 100,000 to 0.31 per 100,000 (a decrease of 42.59%, AAPC = −1.75%), and the age-standardized DALY rate (ASDR) dropped from 13.99 per 100,000 to 7.61 per 100,000 (AAPC = −1.98%). China achieved significant reductions in mortality and age-standardized DALYs, in contrast to relatively stagnant global trends. The effects of age and gender on the disease burden varied: incidence rates remained high among younger populations, while the elderly accounted for the majority of deaths. Overall disease burden was higher in males than females; however, among individuals over 65 years old, the burden was more pronounced in females compared to males.ConclusionFrom 1990 to 2021, China has made progress in controlling mortality. However, the continuously rising age-standardized incidence rate (ASIR) and age-standardized prevalence rate (ASPR) highlight an urgent need for targeted metabolic risk interventions among the youth. The observed epidemiological transition—characterized by a peak in incidence among younger populations and a concentration of deaths in older adults—calls for integrated strategies including early-life lifestyle interventions and comprehensive management frameworks for comorbidities in the elderly. Given China’s large and aging population, addressing these shifting disease patterns remains a major public health challenge.